Transformasi Pengawasan Kewajiban Penggunaan Merek Terdaftar melalui Penerapan Statement of Use, Declaration of Use, dan Specimen of Use - Zaki Akbar Karim; Rika Ratna Permata; Ranti Fauza Mayana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This research aims to analyze the urgency of implementing Statement of Use, Declaration of Use, and Specimen of Use instruments as a means of supervising trademark use obligations in Indonesia. Currently, Law Number 20 of 2016 concerning Trademarks and Geographical Indications (UU MIG) only requires a written statement of use without being accompanied by concrete evidence at the time of renewal applications. This creates a loophole for trademark registrations without the intent to use (non-use), which can hinder bona fide applicants. This study employs a normative legal research method with a comparative law approach between the UU MIG and the Lanham Act (U.S. Trademark Act of 1946). The Lanham Act mandates proof of actual trademark use through a Statement of Use for intent-to-use applications, as well as a Declaration of Use for applications based on use-in-commerce, which must be submitted with a Specimen of Use as actual evidence of the trademark's use in trade. The results indicate that the adoption of these instruments into the Indonesian legal system is urgent to strengthen the supervisory function of the Directorate General of Intellectual Property (DGIP). This implementation would enable the DGIP to conduct administrative (ex-officio) trademark cancellations for non-use, thereby purging the trademark database of passive marks without having to rely on third-party lawsuits. This legal reform is in line with the legal development theory to encourage business actors to actively utilize the economic functions of trademarks.